Social Climber Phenomena As A Lifestyle For Indonesian Communities - Rohmah, Siti; Nur Fitri, Alifa (KOMUNIKA, 2023)
Several social climbing actions or social climbers by artists, celebrities, public figures, and ordinary people often shock the public's attention. The form of social climber usually done by the community is to show off branded goods, wealth, partners, and so on. This study aims to determine the phenomenon of a social climber as a lifestyle for the people of Indonesia. The method used is a qualitative method with a literature study. Data analysis was carried out using a systematic literature review technique in which the research interprets studies related to social climbers as a lifestyle. The results of this study indicate that the social climber is used as a lifestyle for the Indonesian people to get recognition and attention.